(untitled) (Conference on English Language Teaching, 2023)
The trend to use ICT in teaching and learning has become a standard in many educational institutions. Educators consider ICT a requirement and believe that education needs to catch up with technology development. This paper summarizes key messages of integrating Information and Communication Technology (ICT) in education. This paper discusses the potential challenges educational institutions face, particularly teachers when they intend to use technology in the teaching and learning process. The benefits of technology in education are also elaborated. ICT inclusion in education provides advantages not only to the teachers and students but also to the school. This paper provides some basic information for policymakers, education specialists, ICT practitioners and a broader audience interested in the need for technology in the education system.